Impact of Ethical Leadership and Leader–Member Exchange on Whistle Blowing: The Moderating Impact of the Moral Intensity of the Issue - Bhal, Kanika T.; Dadhich, Anubha (2011)
Given the prevalence of corporate frauds and the significance of whistle blowing as a mechanism to report about the frauds, the present study explores the impact of ethical leadership and leader–member exchange (LMX) on whistle blowing. Additionally, the article also explores the moderating role of the moral intensity [studied as magnitude of consequences (MOC)] of the issue on this relationship. The article reports results of three experimental studies conducted on the postgraduate students of a premier technology institute in India. Ethical leadership, LMX, and moral intensity are manipulated through scenarios. Study one (n = 81) manipulates ethical leadership (ethical/unethical) and quality of LMX (low and high) as independent variables; study two (n = 80) manipulates ethical leadership and moral intensity (high and low MOC), and study three (n = 87) manipulates LMX and MOCs to assess their individual and joint effects on whistle blowing. Results show that not only do ethical leadership and LMX predict whistle blowing, but these relationships get moderated by the moral intensity of the issue as well.
Keywords: Moral intensity of the issue (magnitude of consequences); Leader–member exchange; Ethical Leadership; whistle blowing